Faktor – Faktor yang Berpengaruh Terhadap Kinerja Keuangan (Studi Pada Perusahaan Manufaktur 2018 – 2020) - Sri Retnoningsih; Endang Retno Setyoningsih; Maudina Alfiyah; Hamim Furqon; Moh Faqih Ridlo (AKSES: Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to analyze the effect of environmental accounting, leverage anda firm size on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020. There are 230 research samples. The technique for processing the data uses multiple linear regression using the SPSS version 22 application. Simultaneously, it shows that environmental accounting, leverage, firm size have an effect on financial performance. Partially shows that environmental influences financial performance, while leverage and firm size have on effect on financial performance. Keywords: Environmental Accounting, Leverage, Firm Size, Financial Performance